Medo de dentista em cena: uma análise de produções cinematográficas - Oliveira, Aline Louise da Silva (2007)
The fear related to dental procedures can be acquired through disturbing experiences and/or negative cultural influences related in experiences of previous generations. Such influences may be present in diverse forms of cultural expression: in the cinema, plastic arts, music, literature, and diverse vehicles of printed and visual media. This research aimed investigates the images of fear related to the dental service and dentist in motion pictures. The study has qualitative approach, which used the documentary analysis of movies. The data collection was accomplished through research in the Internet by means of the Google tool (http://www.google.com.br), using the describing words filme and dentista . A total of 44 films were found. Of these, after selective criterion for films with scenes showing interaction between dentist and patient in the execution of clinical procedure, only 24 films were enclosed. Then, these were registered in data base created for this research. After second selective criterion of inclusion (scenes with suggestion of dental anxiety), 15 films remained. As regards cinematographic gender, the films with scenes showing "dental anxiety" varied between comedy (8), horror (3), drama (2), thriller (1) and childish (1). Of these films, scenes with images of situations that suggest fear of the dentist and his job were selected and described. The images were categorized by the identification of negative characteristics that incite "dental anxiety". Then, the classification of the categories was proceeded detaching the most recurrent characteristics in the scenes: situation of fear in the waiting-room; pain; instrument coarse/rudimentary; coarseness of the dentist; torture; and low qualification technique. The waiting-room was observed as a place of great tension, due to the noises coming from the dental attendance. The pain related to the Dentistry was the predominant subject in the majority of films (14), associated to others negative characteristics. The rudimentary aspects of procedures and instruments, and the coarse attitudes of the professional could be observed too. The dentist was characterized as confused, sadist, violent, insensitive, incompetent person and disturbed. Such results suggest that, despite the technological advances of the profession, the image of the dentist and his job is still transmitted in a negative way aspect and reinforces the dental anxiety